De novo 9q gain in an infant with tetralogy of Fallot with absent pulmonary valve: Patient report and review of congenital heart disease in 9q duplication syndrome. (19th August 2015) - Amarillo, Ina E.; O'Connor, Shawn; Lee, Caroline K.; Willing, Marcia; Wambach, Jennifer A.
Abstract : Genomic disruptions, altered epigenetic mechanisms, and environmental factors contribute to the heterogeneity of congenital heart defects (CHD). In recent years, chromosomal microarray analysis (CMA) has led to the identification of numerous copy number variations (CNV) in patients with CHD. Genes disrupted by and within these CNVs thus represent excellent candidate genes for CHD. Microduplications of 9q (9q+) have been described in patients with CHD, however, the critical gene locus remains undetermined. Here we discuss an infant with tetralogy of Fallot with absent pulmonary valve, fetal hydrops, and a 3.76 Mb de novo contiguous gain of 9q34.2‐q34.3 detected by CMA, and confirmed by karyotype and FISH studies. This duplicated interval disrupted RXRA (retinoid X receptor alpha; OMIM #180245) at intron 1. We also review CHD findings among previously reported patients with 9q (9q+) duplication syndrome. This is the first report implicating RXRA in CHD with 9q duplication, providing additional data in understanding the genetic etiology of tetralogy of Fallot, CHD, and disorders linked to 9q microduplication syndrome. This report also highlights the significance of CMA in the clinical diagnosis and genetic counseling of patients and families with complex CHD. © 2015 Wiley Periodicals, Inc.